The Role Of Leadership Styles On Staffs Job Satisfaction In Public Organizations - Al-maaitah, Dirar AbdelAziz; Majali, Tha’er; Alsoud, Malek; Al- maaitah, Tamara Adel (The journal of contemporary issues in business and government, 2021)
Job satisfaction is a very important factor among the employees of Public Universities. Job satisfaction is considered an internal principle created by various elements found within a work environment. Due to the influence of various items on job satisfaction, educational organizations should be conscious of implementing the right leadership styles. However, the lack of attention given to this organizational behavior has led to the rise of abnormal reactions among employees. Thus, the current paper focused on the essential role of leadership styles in improving job satisfaction among the employees of Public Universities. Substantial attention should be dedicated to the precise leadership style practiced in an organization. In the same way, specific leadership styles, as external factors, have an important impact on the job satisfaction of employees at Public Universities, because these styles can improve the employees’ commitment to the organizations. This initiative involves enhancing satisfaction among employees and finding an effective leadership style, which is one of the main components of improving educational organizations.